Effect of Age on Production Performance, Egg Geometry and Quality Traits of Lakha Variety of Aseel Chicken in Pakistan - Muhammad Usman; Atia Bashir; Muhammad Akram; Imran Zahoor; Athar Mahmud (Journal of Basic & Applied Sciences, 2014)
Aseel chicken is indigenous to Asian subcontinent famous for its vigor, body characteristics and fighting behavior. Moreover, these birds are also able to withstand harsh climatic conditions of tropical and sub-tropical areas but its rearing is getting less importance due to its poor egg production. The present study was conducted to evaluate the effect of age on production performance, egg geometry and egg quality traits of Lakha variety of Aseel maintained under standard managemental conditions at Indigenous Chicken Genetic Resource Center (ICGRC), University of Veterinary and Animal Sciences, Lahore, Pakistan. For this purpose, a total of 42 birds, 14 birds in each of the following age group (30, 70 and 110 week), were kept up to four months. Collected data were analyzed under Completely Randomized Design (CRD) with comparison of means using Fisher’s LSD test. Statistical analyses revealed significantly higher egg production and egg mass in first age group (30 week), higher egg weight in third age group (110 week) and better FCR/ dozen eggs and FCR/ kg egg mass in second (70 week) and third age (110 week) groups with non-significant differences in feed intake. Regarding egg geometry, all parameters were significantly higher in third age group than that of second and first age groups. In egg quality, Haugh unit score was significantly higher in third age group while yolk index and shell thickness showed non-significant differences among all age groups. So it can be concluded that with increasing age, egg production and egg mass decreases with increase in egg geometry traits.